“An End to a Means”: How DNA-End Structure Shapes the Double-Strand Break Repair Process - Serrano-Benítez, Almudena; Cortés-Ledesma, Felipe; Ruiz, Jose F. (Frontiers in Molecular Biosciences, 2020)
Endogenously-arising DNA double-strand breaks (DSBs) rarely harbour canonical 5’-phosphate, 3’-hydroxyl moieties at the ends, which are, regardless of the pathway used, ultimately required for their repair. Cells are therefore endowed with a wide variety of enzymes that can deal with these chemical and structural variations and guarantee the formation of ligatable termini. An important distinction is whether the ends are directly “unblocked” by specific enzymatic activities without affecting the integrity of the DNA molecule and its sequence, or whether they are “processed” by unspecific nucleases that remove nucleotides from the termini. DNA end structure and configuration, therefore, shape the repair process, its requirements, and importantly its final outcome. Thus, the molecular mechanisms that coordinate and integrate the cellular response to blocked DSBs, although still largely unexplored, can be particularly relevant for maintaining genome integrity and avoiding malignant transformation and cancer.